ZFP217 regulates adipogenesis by controlling mitotic clonal expansion in a METTL3-m(6)A dependent manner - Liu, Qing (RNA Biol, 2019)
Obesity is becoming a global problem. Research into the detailed mechanism of adipocyte development is crucial for the treatment of excess fat. Zinc finger protein 217 plays roles in adipogenesis. However, the underlying mechanism remains unclear. Here, we demonstrated that ZFP217 knockdown prevented the mitotic clonal expansion process and caused adipogenesis inhibition. Depletion of ZFP217 increased the expression of the m(6)A methyltransferase METTL3, which upregulated the m(6)A level of cyclin D1 mRNA. METTL3 knockdown rescued the siZFP217-inhibited MCE and promoted CCND1 expression. YTH domain family 2 recognized and degraded the methylated CCND1 mRNA, leading to the downregulation of CCND1. Consequently, cell-cycle progression was blocked, and adipogenesis was inhibited. YTHDF2 knockdown relieved siZFP217-inhibited adipocyte differentiation. These findings reveal that ZFP217 knockdown–induced adipogenesis inhibition was caused by CCND1, which was mediated by METTL3 and YTHDF2 in an m(6)A-dependent manner. We have provided novel insight into the underlying molecular mechanisms by which m(6)A methylation is involved in the ZFP217 regulation of adipogenesis.